The Role of Da'i Kamtibmas in Community Police Partnership Forum through Religious Moderation - Sarji Sarji; Budi Permana Yusuf; Ardianto Bayu Wibowo (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
The relationship and collaboration between preachers (da'i) and the police is an interesting topic of discussion, especially since there are many cases of terrorism in the name of religion. This article aims to reveal the important role of Da'i Kamtibmas (public security and order) who are members of the FKPM (police and community partnership forum) in strengthening religious moderation in society. This study uses an ethnographic method, several characteristics, namely: exploring or researching social phenomena, unstructured data; few cases or samples; and carried out data analysis and interpretation of data about the meaning of human action. The results showed that the involvement of Da'i Kamtibmas in FKPM was to combat radicalism, extremism, intolerance and terrorism in order to synergize and collaborate with the government and the police in creating security and public order. Therefore, Da'i Kamtibmas need to be equipped with certain standard human resources capabilities such as communication and management skills. So that the preacher can give lectures and advice in accordance with the context of the problem, and can be a mediator between the community and the police.Relasi dan kolaborasi antara pendakwah (da’i) dengan kepolisian menjadi tema pembahasan menarik, terlebih karena munculnya banyak kasus terorisme atas nama agama. Artikel ini bertujuan untuk mengungkap peran penting Da’i Kamtibmas (keamanan dan ketertiban masyarakat) yang tergabung dalam FKPM (forum kemitraan polisi dan masyarakat) dalam memperkuat moderasi beragama di masyarakat. Penelitian ini menggunakan metode etnografi dengan beberapa karakteristik, yaitu: menggali atau meneliti fenomena sosial, data tidak terstruktur; kasus atau sampel sedikit; dan dilakukan analisis data dan interpretasi data tentang arti dari tindakan manusia (human action). Hasil penelitian menunjukkan bahwa keterlibatan Da’i Kamtibmas dalam FKPM adalah untuk memerangi radikalisme, ekstremisme, intoleransi dan terorisme dalam rangka bersinergi dan berkolaborasi pemerintah dan kepolisian dalam menciptakan keamanan dan ketertiban masyarakat. Karenanya, Da’i Kamtibmas perlu dibekali dengan kemampuan standar SDM tertentu seperti kemampuan komunikasi dan manajemen. Sehingga da’i tersebut dapat memberikan ceramah dan nasihat sesuai dengan konteks permasalahan, serta dapat menjadi mediator antara masyarakat dengan kepolisian.